Racial Difference and the Colonial Wars of 19th Century Southeast Asia - Carey, Peter (Peter B.R.), 1948-; Noor, Farish A., 1967- (Book collections on Project MUSE., 2020)
The colonisation of Southeast Asia was a long and often violent process where numerous military campaigns were waged by the colonial powers across the region. The notion of racial difference was crucial in many of these wars, as native Southeast Asian societies were often framed in negative terms as 'savage' and 'backward' communities that needed to be subdued and 'civilised'. This collection of critical essays focuses on the colonial construction of race and looks at how the colonial wars in 19th century Southeast Asia were rationalised via recourse to theories of racial difference, making race a factor in the wars of Empire. Looking at the colonial wars in Java, Borneo, Indochina, Philippines and other parts of Southeast Asia, the essays examine the manner in which the idea of racial difference was weaponised by the colonising powers and how forms of local resistance often worked through such colonial structures of identity politics. Bron: Flaptekst, uitgeversinformatie.